Anti-Obesity Properties of Black Pepper (Piper nigrum): Completing Puzzle using Computational Analysis - Lailiyah, Nurun Nafi'atul; Ibrahim, Mutiara Dwirosita; Fitriani, Chunafa Ayu; Hermanto, Feri Eko (JSMARTech: Journal of Smart Bioprospecting and Technology, 2021)
Pepper (Piper nigrum) is one of the most common spices found in almost every food. Current knowledge informed that pepper regulates physiological activity in obesity. However, the exact mechanism is still poorly understood. This study determined the potential of piperine and piperidine as major compounds in pepper as GHSR-Ghrelin inhibitors due to over-activity of Ghrelin as appetite hormone in obesity. Molecular docking was performed to simulate the binding pattern of piperine and piperidine as GHSR-Ghrelin antagonist. The result showed that piperidine has a lower potential as GHSR-Ghrelin antagonist than piperine based on binding energy calculation and amino acid interaction. Further, piperine binding to GHSR could shift the Ghrelin binding site to the GHSR. In conclusion, piperine may act as an inhibitor of GHSR-Ghrelin interaction to prevent appetite behavior resulting in bodyweight loss in obesity.Â Â